Pyrene Metabolism By New Species Isolated From Soil Rhizoctonia Zeae Sol3 - Ameer Badr Khudhair; Tony Hadibarata; Abdull Rahim Mohd Yusoff; Zee Chuang Teh; Liyana Amalina Adnan; Hesam Kamyab (Springer, 2024)
Rhizoctonia zeae SOL3 fungus was isolated from contaminated soil based on its ability to decolorize remazol brilliant blue R in solid medium. This fungus has been used to degrade pyrene a four-ring polycyclic aromatic hydrocarbon. R. zeae SOL3 could biodegrade pyrene as a sole source of carbon and energy. Different parameters were investigated to study their effect on the biodegradation rate. The highest biodegradation rate reached at 28 °C, non-agitated culture, 20 g/L glucose, 24 g/L NaCl, and 20 mg/L pyrene. The metabolites of pyrene were detected by thin layer chromatography (TLC) and confirmed by gas chromatography–mass spectrometry (GC-MS), which were identified as benzoic acid, 4-hydroxybenzoic acid and botanic acid.